The 1.5 bit-per-stage 10-bit pipelined CMOS A/D converter for CMOS image sensor - Menssouri, Aicha; El Khadiri, Karim; Tahiri, Ahmed (Institute of Advanced Engineering and Science, 2023)
This paper presents a 1.5-bit/stage pipeline analog-to-digital converters (ADC) with a 100 MHz operating frequency for CMOS image sensors built using TSMC 90nm CMOS technology. The design features a novel architecture including a comparator, CMOS transmission gates, a sub-ADC logic circuit, bootstrap switches, and a gain-boosted fully differential telescopic op-amp based switched-capacitor MDAC. The ADC operates on a 1.8 V power supply, with a typical power dissipation of 1.632 mW, and a full-scale input signal voltage of 0.8 V. At 100 MHz sampling frequency, it achieves a maximum ENOB of 12.42 bits, an SNR of 76.53 dB, and a FOM of 0.297 pJ/conversion step. This 1.5-bit/stage pipeline ADC is well-suited for CMOS image sensors.